Transformational leadership and social identity as predictors of team climate, perceived quality of care, burnout and turnover intention among nurses. Issue 6 (5th September 2016) - Cheng, Cindy; Bartram, Timothy; Karimi, Leila; Leggat, Sandra
Abstract : Purpose: The purpose of this paper is to examine the role of transformational leadership (TL) in developing social identity and its subsequent impact on team climate, intention to leave, burnout and quality of patient care among nurses. Design/methodology/approach: Data for this cross-sectional study were collected from a sample of 201 registered nurses in Australia through questionnaires. Structural equation modelling was used to test the hypotheses. Findings: Results illustrate that social identification appears to be the psychological mechanism through which TL impacts important employee outcomes, including perceived quality of patient care. Practical implications: This study provides valuable insights into understanding the critical role of human resource management (HRM) practice and policy in healthcare environments. Findings from this study indicate that human resource managers can assist nurse unit managers to deliver their HRM roles effectively when adequate support and relevant HRM infrastructures are put in place. Originality/value: This research considers the role of first-line nurse managers in healthcare organisations. It provides evidence-based knowledge about the type of leadership style required to achieve desirable employee outcomes and the essential HRM opportunities to facilitate this.